Business models and editorial strategy: the case on the wsj.com - Vara Miguel, Alfonso (2022)
The current research on media business models is characterized by a very high grade of experimentation and the absence of unique answers to the monetization of digital contents. In this landscape, the model of The Wall Street Journal tends to be mentioned as a reference of subscription's model. This paper shows how the most prestigious financial newspaper of the world relies on an hybrid model in which the free content represents the 73% of the whole content included in his website. Furthermore, this paper examines the main traits of the news put behind the daily's paywall, in contrast to the main characteristics of free content.